A community of character : toward a constructive Christian social ethic - Hauerwas, Stanley, 1940- (University of Notre Dame Press, 1981)
"Recognized as a leading theological ethicist, Stanley Hauerwas applies his theory of the narrative formation of Christian character to the field of social ethics. He advances his ideas by showing why any consideration cannot be divorced from the kind of community the church is and should be. He also challenges the dominant assumption of contemporary Christian social ethics that there is a special relation between Christianity and some form of liberal democratic social system."--Publisher's description.